Hubungan Pengetahuan Gizi dan Kebiasaan Makan dengan Status Gizi pada Remaja SMA Negeri 2 Merangin - Heni Heni; Filius Chandra; Merita Merita (3031-8572, 2022)
Adolescence is a group that is vulnerable to various nutritional problems such as undernutrition and overnutrition, the influence of nutritional promlems on growth, development, intellectual and productivity shows the large role of nutrition. Therefore, the purpose of this study was to analysis the relationship between nutritional knowledge and eating habits with nutritional status in adolescents at SMAN 2 Merangin in 2022. This research is an analysis study with a cross sectional study design which was carried out at SMAN 2 Merangin in 2022. The population in this study was 381 adolescents with a sample of 79 adolescents with by purposive sampling technique . Data collection was carried out using a questionnaire. Statistical analysis used is univariate and bivariate analiysis. Based on univariate analysis, most of the adolescents at SMAN 2 MERANGIN had knowledge of nutrition which was classified as poor 48 (61%), good eating habits 51% (65%) and nutritional status classified as good 58 (73,4%). Chi-square analysis shows that there is no relationship between nutritional knowedge and nutritional status (P-Value=0,900) and there is no relationship between eating habits and nutritional status (P-Value=0,442). can be concluded that there is no significant relationship between nutritional knowledge and eating habits with nutritional status.